2017
DOI: 10.3389/fnagi.2017.00167
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Adaptations Induced by Gentle Physical Activity Are Reduced Among Older Women

Abstract: The aim of this study was to compare the ability of older individuals to maintain an efficient upright stance in contexts of vestibular sensory manipulation, according to their physical activity status. Two groups of healthy older women (aged over 65) free from any disorders (i.e., neurological, motor and metabolic disorders) and vestibular disturbances, participated in this study. One group comprised participants who regularly practiced gentle physical activities, i.e., soft gym, aquarobic, active walking, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is possible that dizziness experienced by the older adults with NP in this study may be due to sensory conflicts between the cervical spine and vestibular afferents (Hikosaka & Maeda, 1973) which in turn increased their fear of movement. Further, previous study showed that the efficiency of postural regulation diminishes with age (Maitre & Paillard, 2017). Our study provides a basis for future interventional studies to determine whether addressing the anxiety of the fear of neck movements and treating the cervical spine dysfunction will improve dynamic postural control and potentially reduce the risk of falls.…”
Section: Dynamic Postural Controlmentioning
confidence: 57%
See 1 more Smart Citation
“…It is possible that dizziness experienced by the older adults with NP in this study may be due to sensory conflicts between the cervical spine and vestibular afferents (Hikosaka & Maeda, 1973) which in turn increased their fear of movement. Further, previous study showed that the efficiency of postural regulation diminishes with age (Maitre & Paillard, 2017). Our study provides a basis for future interventional studies to determine whether addressing the anxiety of the fear of neck movements and treating the cervical spine dysfunction will improve dynamic postural control and potentially reduce the risk of falls.…”
Section: Dynamic Postural Controlmentioning
confidence: 57%
“…Maitre et al (2013) (Maitre & Paillard, 2017), age was positively associated with the CoP velocity within the moderate frequency. However, it is difficult to meaningfully interpret the rest of the results of the wavelet analysis as our results did not give clarity or give further insights to the complex mechanisms that underlie postural control deficits in NP.…”
mentioning
confidence: 91%